2013
DOI: 10.5012/bkcs.2013.34.8.2330
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymers for Solid-Phase Extraction of Sarcosine as Prostate Cancer Biomarker from Human Urine

Abstract: A highly selective molecularly imprinted polymer (MIP) for sarcosine, a cancer marker, was prepared and its use as solid-phase extraction (SPE) sorbent material was demonstrated. The MIP was prepared by a very simple procedure using methacrylic acid as functional monomer and a mixture acetonitrile/water (4/1, v/v) as porogen, overcoming in this way the problems usually related to the imprinting of biological polar compounds. The MIP was tested in batch experiments in order to evaluate its binding properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…SPE based on molecular imprinting polymers is an efficient and selective method for preconcentration and separation of analytes . Grafting can be used for molecular imprinting on the surface of polymer/silica beads and the resulting MIP composites have the advantages of more accessible binding sites and faster mass transfer compared to the MIPs prepared by using conventional bulk polymerization techniques.…”
Section: Resultsmentioning
confidence: 99%
“…SPE based on molecular imprinting polymers is an efficient and selective method for preconcentration and separation of analytes . Grafting can be used for molecular imprinting on the surface of polymer/silica beads and the resulting MIP composites have the advantages of more accessible binding sites and faster mass transfer compared to the MIPs prepared by using conventional bulk polymerization techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The inherent selectivity associated with molecularly imprinted polymers (MIPs) has made them efficient materials for use in the SPME technique. This combination has been successfully employed for extraction and preconcentration of various analytes from different samples [6,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, an increasing number of metabolomics research shows that bodily fluid metabolites also may serve as a marker for early detection or monitoring of a variety of tumor progression, such as breast cancer, colon cancer, liver cancer, stomach cancer, prostate cancer [11]. Over the years, the early discovery and early diagnosis of malignant tumors has been a lot of research and found a number of serum tumor markers, and as an important means of diagnosis of cancer, but the presence of serum tumor markers complicated operation, cost high, invasive, early detection rate is not ideal and other factors, is not conducive to tumor mass screening, therefore, found that a drawn convenient, easy operation, non-invasive, and can be used for a broad spectrum of early cancer screening the detection method is very important [12][13]. Easy to collect urine samples and non-invasive, patient compliance is high, so many medical experts and scholars dedicated to the research of cancer urine test, the current detection of the urine is divided into two: one is the detection of dopa, other One is the detection of monohydric phenol derivative.…”
Section: Introductionmentioning
confidence: 99%